Aging profile, adherence to the Elderly Health Handbook and self-perception of health, Ituiutaba-MG (2015 and 2018) - Ferreira Freire, Victor Antonio; Vilarinho Melo, Janyne; de Medeiros Santos, Ana Lúcia; Oliveira Silva, Ériks; Bernardino Neto, Morun; Azenha Alves de Rezende, Alexandre; Calábria, Luciana Karen (Journal of Health Care, 2022)
Studies with elderly people considering the different demographic and socioeconomic profiles are fundamental to understand the dynamics of life expectancy and the formulation of public policies. Objective: To evaluate and compare demographic and socioeconomic variables, adherence to the Elderly Health Handbook and the self-perception of health of the elderly in Ituiutaba-MG in the years 2015 and 2018. Methods: This is a cross-sectional study with 304 elderly people attended at basic health units using a semi-structured questionnaire. Descriptive and inferential statistics using the Mann-Whitney Test and qui-square were used to compare the variables investigated over the interval of three years. Results: There was a transition in the age group from 60-69 years old in 2015 to 70-79 years old in 2018, with prevalence of elderly people with partner and do not live alone. Low education was present in the years evaluated and the prevalent monthly income in 2018 was lower than in 2015. Moreover, low adherence to the Health Record for the Elderly and the reasonable perception of health prevailed between the years evaluated. Conclusion: The findings of this study highlight the necessity to improve the municipal adherence to public health policies aimed at the elderly, ensuring better health monitoring and promoting quality of life.